PENGARUH SISTEM KEUANGAN DESA (SISKEUDES) TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DESA PADA KABUPATEN BOLAANG MONGONDOW TIMUR - Katryn Natania Mega; Lintje Kalangi; Peter M. Kapojos (Universitas Sam Ratulangi, 2022)
The Village Financial System (SISKEUDES) is an application developed by the Financial and Development Supervisory Agency (BPKP) and the Ministry of Home Affairs to help village governments improve the quality of village financial governance. In addition, with better use and control of the village financial system (SISKEUDES) application, village financial management will be more accountable. This study aims to determine whether the village financial system (SISKEUDES) has an effect on the village's financial management accountability. This type of research is called quantitative research. The source of research data used is primary data. The population in this study was all of the Finance Officers from 81 villages in the East Bolaang Mongondow Regency. The data analysis technique used is simple linear regression analysis. The data collection method used is the questionnaire method. The results of this research show that the village financial system (SISKEUDES) has a positive effect on the accountability of village financial management..